A Review of Warm‐Season Turfgrass Evapotranspiration, Responses to Deficit Irrigation, and Drought Resistance. (16th August 2017) - Colmer, Timothy D.; Barton, Louise
Abstract : Knowledge of turfgrass evapotranspiration (ETc ) and drought resistance can enable water conservation by guiding turfgrass selection for various climates and irrigation scheduling. Turfgrass ETc, crop coefficients ( K c = ETc /ET0, where ET0 is reference evapotranspiration), responses to deficit irrigation, and drought resistance, are reviewed for warm‐season species (perennial, sod‐forming, C4 grasses). In well‐watered conditions, ETc was 2.44 to 10.53 mm d −1 (nine species in six climates during late spring to early autumn) and K c was 0.34 to 1.27 (seven species in seven climates). Under deficit irrigation, ETc was 2.14 to 5.71 mm d −1 and K c was 0.52 to 0.94 (seven species in four climates). Crop evapotranspiration was greater with increasing aridity. The K c data provide benchmarks for irrigation. Field irrigation dose–response experiments show that some warm‐season turfgrasses differ in water requirements. Inter‐ and intraspecies variations in drought resistance have also been documented. Additional research is required to elucidate the mechanisms underlying the observed variations in turfgrass ETc and drought resistance and to test the influence of management practices (e.g., cutting height, nitrogen fertilizer, and growth regulators) in field situations. Looking forward, process‐based modeling could increase understanding of turfgrass traits and other factors influencing ETc and drought resistance and further assist efficient use of water in warm‐season turfgrass systems.